Impact of stress hyperglycemia ratio on acute kidney injury and mortality in patients with cardiogenic shock: a retrospective analysis - Cai, An; Zhuang, Liqin; He, Min; Huang, Song; Tong, Jinying (Frontiers in Endocrinology, 2025)
AimsThis study investigated the predictive value of the stress hyperglycemia ratio (SHR) for acute kidney injury (AKI) and mortality in cardiogenic shock (CS).MethodsA retrospective analysis was conducted on patients with CS from the Medical Information Mart for Intensive Care IV database based on SHR values. The primary outcome was AKI incidence, with in-hospital and 90-day mortality as secondary outcomes in the subgroup with AKI. Logistic regression assessed the relationship between SHR and AKI as well as in-hospital mortality, while Cox regression was employed to evaluate 90-day mortality. Restricted cubic spline curves were utilized to explore nonlinear associations.ResultsAmong 378 patients with CS, 56.9% developed AKI. Elevated SHR was associated with a higher risk of AKI (OR 2.58, 95% CI 1.44–4.81). In the AKI subgroup, SHR exhibited a U-shaped relationship with mortality (P for non-linearity < 0.05). An SHR above 1.26 was linked to increased in-hospital (OR 2.74, 95% CI 1.35–5.80) and 90-day mortality (HR 2.84, 95% CI 1.95–4.13).ConclusionsSHR is independently associated with both AKI and mortality in CS. A U-shaped curve suggests that optimal glycemic control may improve patient outcomes. Prospective studies are needed to validate these findings and further investigate SHR as a prognostic marker.